2020
DOI: 10.1002/aws2.1171
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of radium in the Wisconsin Cambrian–Ordovician aquifer system

Abstract: Compliance monitoring of contaminants in public drinking water supplies results in publicly available data sets that are maintained by state agencies and useful for investigating changes in water quality. In this study, spatial and temporal trends in naturally occurring radium (combined 226Ra + 228Ra) concentrations in groundwater from the Midwestern Cambrian–Ordovician aquifer system were evaluated with a Wisconsin Department of Natural Resources compliance data set. Average combined Ra from 2000 to 2018 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Similarly, analysis of long-term trends in combined Ra in municipal wells will be facilitated by more precise measurements. For example, although increasing Ra levels in untreated municipal well water in Wisconsin were recently reported (Dematatis et al, 2020), the results presented here suggest that such long-term trends may have higher noise resulting from a lower analytical precision. That is, water utilities are required to use an EPA-approved analysis (e.g., decay counting) to report combined Ra levels for regulatory compliance.…”
Section: Analytical Implications For Understanding Ra Trends In Drink...mentioning
confidence: 52%
See 1 more Smart Citation
“…Similarly, analysis of long-term trends in combined Ra in municipal wells will be facilitated by more precise measurements. For example, although increasing Ra levels in untreated municipal well water in Wisconsin were recently reported (Dematatis et al, 2020), the results presented here suggest that such long-term trends may have higher noise resulting from a lower analytical precision. That is, water utilities are required to use an EPA-approved analysis (e.g., decay counting) to report combined Ra levels for regulatory compliance.…”
Section: Analytical Implications For Understanding Ra Trends In Drink...mentioning
confidence: 52%
“…In Wisconsin, 116 municipal wells exceeded the Ra MCL at least once from 2019 to 2020 (Wisconsin Department of Natural Resources, n.d.). On a broad geographic scale, combined Ra ([ 226 Ra + 228 Ra]) levels in the MCOAS in Wisconsin are increasing in recent years, although trends vary at the municipal scale (Dematatis et al, 2020). Some municipalities, like the City of Waukesha, Wisconsin, have been forced to seek new sources of drinking water due to elevated levels of Ra and other impacts of historic drawdown in the local aquifer system (Grundl et al, n.d.;Great Lakes-St. Lawrence River Basin Water Resources Council, 2016;Luczaj & Masarik, 2015) even though new sources are expensive and difficult to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…31 A study in Wisconsin revealed increasing Ra concentrations over a 20year period but did not identify a cause of the increase. 32 The results of these studies indicate the need to evaluate the temporal variability of Ra in groundwater.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12,13 Local-scale spatial variability (e.g., within a municipality) in well water quality, combined with annual and decadal temporal variation, also complicates management of municipal well fields. 14 A better understanding of processes controlling naturally occurring contaminant speciation and partitioning within aquifer systems may contribute to maintaining groundwater as a potable water resource. 15,16 Determining the processes controlling the distribution of naturally occurring contaminants within a heterogeneous aquifer is challenging, in part because complex flow paths within regional aquifer systems, and local flow paths impacted by groundwater pumping, affect subsequent contaminant partitioning into the groundwater.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Groundwater is a major source of drinking water worldwide, with an estimated 2.5 billion people relying solely on groundwater for daily water needs . The presence of contaminants affects the quantity of groundwater available for drinking, as degraded water quality dictates overall water availability. , Regulatory and research efforts often focus on prevention and/or remediation of anthropogenic contaminants in groundwater; however, naturally occurring contaminants (e.g., Ra, As) are already present within many aquifer systems and can be mobilized by changes in geochemical conditions. In many cases, water quality is degraded by naturally occurring constituents, increasing water stress within a community and thus requiring expensive water treatment or alternate water sources. , Local-scale spatial variability (e.g., within a municipality) in well water quality, combined with annual and decadal temporal variation, also complicates management of municipal well fields . A better understanding of processes controlling naturally occurring contaminant speciation and partitioning within aquifer systems may contribute to maintaining groundwater as a potable water resource. , …”
Section: Introductionmentioning
confidence: 99%